A Fast Fermi Acceleration at Mars Bow Shock. Issue 7 (24th July 2019) - Meziane, K.; Mazelle, C. X.; Mitchell, D. L.; Hamza, A. M.; Penou, E.; Jakosky, B. M.
Abstract: We report, for the first time, strong evidences that a fast Fermi mechanism is taking place at the Mars bow shock. The MAVEN spacecraft observations from the Solar Wind Electron Analyzer instrument show electron flux spikes with energies up to ∼1.5 keV. These spikes are associated with sunward propagating electrons and appear when the interplanetary field line threading the spacecraft is connected near the Martian bow shock tangency point. The observed loss cone distribution is a salient feature of these backstreaming electrons as the phase space density peaks on a ring centered along the magnetic field direction. Moreover, the data show no evidence of any effect due to a hypothetical cross‐shock electric potential on the observed angular distributions. Although similar distributions are seen at the terrestrial bow shock, the quantitative analysis of the measurements strongly indicates that the electrons are produced at the shock foot and escape upstream before exploring the entire shock structure. Key Points: Flux spikes associated with sunward propagating energetic electrons observed upstream of the Martian bow shock Fast Fermi process operating at the foot of the Martian shock structure rather than the ramp Similarities and strong contrasts with the terrestrial foreshock